Enhanced thermoelectric properties of PEDOT:PSS composites by functionalized single wall carbon nanotubes. (3rd June 2020) - Tonga, Murat; Wei, Lang; Lahti, Paul M.
Summary: This contribution investigates the utilization of carboxylic acid and hydroxyl functionalized single wall carbon nanotubes (SWNTs) for enhancing thermoelectric (TE) performances of the composites prepared with an inherently conductive polymer, poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). Our results indicated an atypical thermoelectric property which is a simultaneous increase in electrical conductivity and the Seebeck coefficient which leads a greater power factor (PF) up to 22 μW m −1 K −2 while it is only 0.7 μW m −1 K −2 for the sample prepared with pristine SWNT. The functionalities on the carbon nanotube walls facilitate blend dispersion in aqueous media without requiring any surfactants and also enhance PFs as a result of improved charge transport routes. The improvement in the thermoelectric performance can be ascribed to hydrogen bonds with the ‐COOH or ‐OH groups on the nanotube walls which help induce the polymer chains to adopt an extended conformation. Abstract : Thermoelectric (TE) properties of PEDOT:PSS increased with added functionalized SWNT. An atypical TE property which is a simultaneous increase in electrical conductivity and the Seebeck coefficient was observed. The functional groups induce the polymer chains to adopt an extended conformation, which enhanced TE performance.